Strategi Pembelajaran berbasis Islam Moderat dalam Menanamkan Nilai Keseimbangan di Madrasah - Maftuh Maftuh; Sa’adatul Awwaliyah (JOURNAL SAINS STUDENT RESEARCH, 2024)
The purpose of this journal is to find out Learning Strategies of Madrasah in instilling Islamic values ​​of moderation which have become a current trend as prevention of radical behavior and racism from an early age. The problems to be answered regarding learning strategies in instilling the value of balance in madrasas are (1) what strategies do teachers use in instilling the value of balance in madrasah? (2) What are the supporting and inhibiting factors for cultivating the value of balance in madrasah? To answer this problem, the researcher used a type of case study research with a descriptive-qualitative method, and This research used observation, interview and documentation techniques as data collection. This study result in the finding that three strategies used in instilling the value of moderation in MI Ma’arif Sidomukti, there are expository learning strategies, cooperative learning strategies and also habituation strategies. There are several factors that support and hinder the cultivation of balance values, such as student conditions and abilities, family factors, community factors and Madrasah facility factors.